Asuhan Keperawatan Gerontik Pada Pasien Hipertensi Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Syaidussiddiq .; Hasmita .; Armaita .; Sandra Dewi (CV. ITTC INDONESIA, 2026)
Based on data from the World Health Organization (2023), an estimated 1.28 billion adults aged 30-79 years worldwide suffer from hypertension, most of whom live in low- and middle-income countries. Hypertension is a major factor leading to cardiovascular diseases such as heart attacks, kidney failure, and stroke. The purpose of this study is for researchers to be able to provide nursing care to elderly people with hypertension. The research method used is a case study, where researchers took 1 patient as a sample. This study was conducted at Wisma Sago PSTW Sabai Nan Aluih Sicincin Padang Pariaman on February 11-16, 2026. After the assessment, the nursing diagnoses were found to be: chronic pain, disturbed sleep patterns and risk of falling. The interventions carried out included the use of pharmacological techniques (administration of amlodipine), non-pharmacological (application of relaxation techniques with deep breathing, autogenic relaxation techniques), and prepared education. After 5 days of implementation, headaches decreased, blood pressure decreased, pain scale decreased, sleep patterns improved, falls while walking decreased. Patients are expected to control their blood pressure by taking antihypertensive medication, managing pain, adopting a healthy lifestyle with regular exercise, and avoiding anything that could worsen their condition. Caregivers are expected to monitor and accompany patients in carrying out the care they have been taught, and to remind them to have their blood pressure checked regularly at the home's clinic.